Implementation of The Cash and Carry Method Towards Direct Household Economic Improvement in Bricks Sales in Bontobiraeng Village, Gowa Regency, Indonesia - Fitriani Mandung; Serlin Serang (Golden Ratio of Community Services and Dedication, 2026)
This study aims to analyze the application of the cash-and-carry method to directly improve household economic performance in brick sales in Bontobiraeng Village, Gowa Regency. The research method used was a descriptive, quantitative approach, with data collected through observation, interviews, and questionnaires distributed to 82 brick entrepreneurs and producers. The results indicate that implementing the cash-and-carry sales system has a positive and significant impact on increased income, faster capital turnover, and household economic stability for entrepreneurs and brick producers. The cash-and-direct-delivery payment system significantly helps entrepreneurs minimize bad debts, optimize working capital, and sustainably meet household needs. Thus, the cash-and-carry method has proven effective for entrepreneurs and brick producers in Bontobiraeng Village.